2021
DOI: 10.3390/en14227653
|View full text |Cite
|
Sign up to set email alerts
|

Wake Expansion and the Finite Blade Functions for Horizontal-Axis Wind Turbines

Abstract: This paper considers the effect of wake expansion on the finite blade functions in blade element/momentum theory for horizontal-axis wind turbines. For any velocity component, the function is the ratio of the streamtube average to that at the blade elements. In most cases, the functions are set by the trailing vorticity only and Prandtl’s tip loss factor can be a reasonable approximation to the axial and circumferential functions at sufficiently high tip speed ratio. Nevertheless, important cases like coned or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…It should be noted, that in this section, the wind turbine wake is treated as a helix with constant radius while the wake expands behind a real wind turbine. However, Wood 26 demonstrates that the approximation of the Kawada‐Hardin equation for the axial induced velocity presented, here, remains accurate when compared to a Biot‐Savart evaluation of an expanding wake.…”
Section: Sweep Correction Modelmentioning
confidence: 81%
“…It should be noted, that in this section, the wind turbine wake is treated as a helix with constant radius while the wake expands behind a real wind turbine. However, Wood 26 demonstrates that the approximation of the Kawada‐Hardin equation for the axial induced velocity presented, here, remains accurate when compared to a Biot‐Savart evaluation of an expanding wake.…”
Section: Sweep Correction Modelmentioning
confidence: 81%
“…Simple and accurate approximations to the KH solutions are described in and were used to analyse the effects of low λ by Wood et al (2016) and Vaz & Wood (2016), and blade sweep by Fritz et al (2022). Wood (2021) showed that the expansion of the trailing vortices in the wake of a real turbine is easily accounted for in the approximations to the KH equations. The present analysis implies that the remaining restriction of the KH equations to constant p is not significant.…”
Section: The Constancy Of Vortex Pitchmentioning
confidence: 99%
“…Nearly all BEMT codes for wind turbines use Prandtl's tip loss factor, F P to approximate F u and F w . Some of the inaccuracies of using F P are documented in Wood et al (2016) and Wood (2021), while reviewed the numerical methods that produce accurate estimates for F u and F w . Wood et al (2016) showed that F u , F w → F p and F p → 1 as λ increases, suggesting that azimuthal variations become less important in the high-thrust region.…”
Section: Introductionmentioning
confidence: 99%